Аналіз результатів педагогічного експерименту з формування комунікативної компетентності майбутніх інженерів - Бутенко (Солодовник), Тетяна Олександрівна (НТУ "ХПІ", 2012)
In the article the results of forming experiment on communicative competence formation of future engineers are compared. Comparative analysis of control and experimental groups testifies the efficiency of the offered pedagogical technology on communicative competence formation of future engineers
Keywords: підготовка висококваліфікованих фахівців; комунікативна компетентність; педагогічні технології; комунікативно-діяльнісний компонент; монологічне мовлення; ділова гра